Answer:
x=3, 4, or 5
Explanation:
![x^3 − 12x^2 + 47x − 60=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ri47wg1ogcadgpy2wcmzss4ewtmjwbcked.png)
First we have to determine one value of x by hit and trial method for which , the above polynomial becomes 0
on trying random values of x , we sees that for x = 3 , the polynomial becomes 0
Hence (x-3) is one of the factor
Hence now let us move with the factorization part
The above polynomial can be re written as
![x^2(x-3)-9x(x-3)+20(x-3)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/mnjf1r815xf41fy6gtjw4saqvithrljby3.png)
![(x-3)(x^2-9x+20)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/3izwkk60g4tv16vwuyqrrgmw1zvrustmnj.png)
![(x-3)(x^2-5x-4x+20)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/26h1h367gdqwnd8vh421p493yhf1gvo2jj.png)
![(x-3)(x(x-5)-4(x-5))](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ys6xywtdbwzmh91kvqu846vr46klv4153p.png)
![(x-3)(x-5)(x-4)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/4361dukhibs8018fr72s04709sdi7w1zbk.png)
hence we have our
![f(x) = (x-3)(x-5)(x-4)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/tddbuwedoo98y95ocnhhka4sjoz119m8x1.png)
In order to find the zeroes we put f(x) =0
Hence
[tex](x-3)(x-5)(x-4)=0
Therefore
if (x-3)=0 , x=3
if (x-5) , x= 5
if (x-4), x=4